Comparison of rational pharmacotherapy decision-making competence of general practitioners with intern doctors - AKICI, AHMET; KARAALP, ATİLA; UĞURLU, MUSTAFA ÜMİT (SPRINGER HEIDELBERG, 2004)
Objective. The aim of this study was to compare rational pharmacotherapy decision-making competency of interns (final-year medical students) who had received rational pharmacotherapy education (RPE), with their classmates at another medical school and general practitioners (GPs) who had not been exposed to RPE. Design. A written, objective, structured clinical examination (OSCE), consisting of open and structured questions, was given to all participants. The participants were expected to make a treatment plan and prescribe for simple, uncomplicated beta-hemolytic streptococcal tonsillitis and mild-to-moderate essential hypertension patients, explain their proposed treatment plans and reasons affecting their drug choice. After the OSCE, a questionnaire to assess knowledge of the rational use of drugs was given to the participants. Results. Fifty RPE(+) interns, 54 RPE(-) interns and 53 GPs participated in the study. Mean scores of RPE(+) interns were higher than those of GPs, which were in turn found to be higher than those of RPE(-) interns for all cases. The RPE(+) interns scored the highest regarding all components of rational pharmacotherapy process for all cases of both indications. However, participants in all groups had higher scores for the structured questions compared with the corresponding open ones for both diseases. Prescription analysis also revealed better results for RPE(+) interns regarding the number of drugs/prescription and treatment costs. Conclusion. The present study demonstrated that the final-year medical students (interns) markedly benefited from undergraduate RPE at the medical school in developing rational prescribing skills compared with their classmates from a medical school with traditional pharmacology education. Interestingly, they got higher scores than not only RPE(-) interns, but also than the GPs participating in this study, indicating the urgent need for continuous medical education programs in this field throughout the country for practicing GPs.
Keywords: therapeutic competence; medical students; general practitioner; CLINICAL-PHARMACOLOGY; DRUG-TREATMENT; IMPROVE; INTERVENTION; EDUCATION; IMPACT